Does Green Energy Investment Effects on Islamic and Conventional Stock Markets? New Evidence from Advanced Economies - Avazkhodjaev, Salokhiddin; Dhiensiri, Nont; Mukhamedov, Farkhod (International Journal of Energy Economics and Policy, 2024)
This study investigates the long-run and short-run nexus between renewable energy investment, and Islamic and conventional stock markets in advanced economies, namely the United States, United Kingdom, and European Union over the period from January 1, 2002 to August 1, 2023. The study uses the Nonlinear Autoregressive Distributed Lag (NARDL) model to examine the long-run and short-run asymmetric effects between selected variables under study. The results of empirical model estimation suggested that the green energy investment adjustment is running towards the long- and short-run steady increment regarding positive and negative shocks in conventional and Islamic stock markets. Indeed, the shocks of the green energy investment on conventional stock markets of the US and EU are positively asymmetric in the long run; the UK has an insignificant effect in the long run. Importantly, green energy investment positively has significant effects on conventional and Islamic stock markets in the US. UK and EU (except the conventional stock market of the US). The short-run coefficients of green energy investment have a significant positive effect on Islamic stock markets for the selected U.S, UK, and EU markets. Likewise, the EU conventional stock market has a significant positive effect in the short run. Change in green energy investment has a negatively insignificant impact on Islamic and conventional markets of the EU and the UK. Indeed, short-run coefficients of green energy investment negatively on the U.S. conventional stock market. The increase in green energy investment may result in an increase in the cost of energy generation, which reduces the renewable energy production firm’s profitability and finally decreases the stock market prices in the short run. These findings have important implications for the portfolio diversification and hedging decisions of environmentally concerned investors. In sum, investors should consider the presence of extreme tail dependence between green investments and stock markets an important factor in making more informed and rational choices.